2013
DOI: 10.1111/are.12180
|View full text |Cite
|
Sign up to set email alerts
|

Water quality influences the presence ofStreptococcus agalactiaein cage cultured red hybrid tilapia,Oreochromis niloticus × Oreochromis mossambicus

Abstract: Attempts were made to identify the association between water quality parameters and the presence of Streptococcus agalactiae in cage cultured red hybrid tilapia, Oreochromis niloticus × O. mossambicus. Fish from commercial floating net cage‐culture systems in a river and lake were randomly sampled over a 24‐month period. Swabs from the brains, eyes and kidneys were streaked directly onto blood agar to isolate S. agalactiae. Water temperature, dissolved oxygen, pH, clarity, ammonia, nitrite, sulfide, rate of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 33 publications
(64 reference statements)
3
41
1
2
Order By: Relevance
“…Other studies have similarly shown that unfavourable water quality in fish farms can influence the susceptibility of cultured red hybrid tilapia to infection with S. agalactiae (Amal et al . ,b). Moreover controlled studies have corroborated this effect, also in tilapia (Evans et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have similarly shown that unfavourable water quality in fish farms can influence the susceptibility of cultured red hybrid tilapia to infection with S. agalactiae (Amal et al . ,b). Moreover controlled studies have corroborated this effect, also in tilapia (Evans et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Amal et al . , ,b; Lusiastuti et al . ) and Gilthead seabream, Sparus aurata Linnaeus in Kuwait (Glibert et al .…”
Section: Introductionmentioning
confidence: 99%
“…Environments with different hydrodynamic conditions can also contributed to the presence of a pathogen. Prevalence of cultured red hybrid tilapia (Oreochromis niloticus x Oreochromis mossambicus) positive for GBS was higher in lake compared to river, and that unfavourable environmental factors such as ammonia, temperature, water clarity, pH, and dissolved oxygen were positively correlated with the presence of GBS in infected fish (Amal et al, 2013a).…”
Section: Group B Streptococcus Is Likely To Be the Cause Of The Diseamentioning
confidence: 99%
“…So whilst we can transfer infection by immersion in a relatively high concentration of bacteria, it appears that better water quality reduces stress in a cohort naïve fish sufficiently to prevent initial colonisation, or reduce shedding in challenged fish. A combination of unfavourable water quality in fish farm can influence the presence of S. agalactiae and the susceptibility of cultured red hybrid tilapia to the bacteria (Amal et al, 2013a). As the environmental drivers for the recent and ongoing mortalities in wild Queensland grouper is unknown this aspect of susceptibility to infection is worthy of further investigation in a controlled study.…”
Section: Transmission Of Gbs Via Water-born Exposure Has Been Previoumentioning
confidence: 99%
See 1 more Smart Citation